A Scale Calibration for Vocational Learning Styles Instrument - Suhaini, Mazlili; Ahmad, Adnan; Mohd Bohari, Normila (International Journal of Psychosocial Rehabilitation, 2020)
Learning styles identify the behaviors and attitudes that decide an individual’s preferred method of learning. An overabundance of learning style literature is more focused on learners in general and has been conceptually elaborated in the literature; however, few empirical data and few appropriate instruments have been carried out on the learning style of vocational students. This article sets out to analyze the development of the Learning Styles of Vocational Student instrument to routinely identify students’ learning styles in the vocational field. Hence, the main objective of this paper is to empirically evaluate the rating scale categories in the instrument that is used to evaluate the students’ learning styles in the vocational field. Guided by quantitative design, the data was collected from 57 respondents from a vocational college in the north of Malaysia. A scale calibration that is based on the Rash Model analysis specifically analyzes the effective rating scale categories. The findings reveal that the instruments function optimally with a four-category Likert scale across all the four dimensions, rather than a five-category structure as was originally intended. For that, it is suggested that the initial five-category Likert scale be modified for the actual study.